PENGARUH TERAPI RADIASI FAR INFRARED TERHADAP INTENSITAS NYERI LUTUT OSTEOARTRITIS PADA LANSIA - Putra, Riko Husada (Coping: Community of Publishing in Nursing, 2014)
Normal 0 false false false EN-US X-NONE X-NONE Osteoarthritis is the most common degenerative joint disease. In osteoarthritis, joint pain is the main symptom that often leads to disability and it is the most frequent reason for osteoarthritis sufferers to seek medical treatment. Reduction in pain intensity as the focus of treatment of osteoarthritis and far infrared radiation therapy provide a more constant heat effect to reduce pain intensity. This study aimed to investigate the effect of far infrared radiation therapy for osteoarthritis knee pain intensity in the elderly. This study is a quasi-experimental study with pretest-posttest control group design. Sample consisted of 34 people (17 treatment group and 17 control group) obtained from consecutive sampling. The data was collected by using interviews with numerical pain scale of 0-10. The results showed the differences in mean scores of pain intensity decrease in both groups. The mean score of pain intensity decrease in treatment group was 2,412 , and the mean score of pain intensity decrease in control group is 1,412. The result of independent t-test statistical test yielded the value p<? (0.004 <0.05), in which there was differences in scores of pain intensity decrease between treatment group and control group. Far infrared radiation therapy had 2 -25 micron of long-wavelength that produce heat effect which has a deeper penetration under the skin, in which it can be concluded that there had been a significant effect of far infrared radiation therapy on the intensity of osteoarthritis knee pain in the elderly at Sanglah General Hospital’s Geriatric Clinic. Based on these results, it is expected that health workers - especially those working at the Geriatric Clinic of Sanglah General Hospital – will plan alternative interventions in the form of far infrared radiation therapy to reduce the intensity of osteoarthritis knee pain on the elderly. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; text-align:justify; line-height:200%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;}
Keywords: Osteoarthritis; far infrared radiation therapy; intensity of pain